PERAN JURNALISME WARGA TERHADAP PERKEMBANGAN HOMELESS MEDIA ( STUDI KASUS PADA AKUN INSTAGRAM @Infolamongan tahun 2024 - Abdurrosyid Robbani; Hadi Ismanto; Siti Mahmudah Yanti (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to examine the role of citizen journalism in supporting the growth of homeless media, using a case study of the Instagram account @infolamongan in 2024. The research employed a qualitative descriptive method with data collection techniques including content observation, interviews with five informants, and digital documentation. The data were analyzed through a source triangulation approach. Findings show that the people of Lamongan actively participate as event reporters, social initiators, digital facilitators, and visual content creators. This participation directly contributes to the growth of the @infolamongan account in terms of follower count, user engagement, and social relevance. The account represents a form of organically-grown homeless media, unaffiliated with formal press institutions, yet effective as a digital public sphere.